Teaching social foundations of education : contexts, theories, and issues - Butin, Dan W. (Dan Wernaa) (Sociocultural, political, and historical studies in education., 2005)
This book is a comprehensive, critical examination of the theory and pedagogy of the field of social foundations of education and its relevance and role within teacher education.